2012
DOI: 10.1002/anie.201108763
|View full text |Cite
|
Sign up to set email alerts
|

Cross Coupling of Acyl and Aminyl Radicals: Direct Synthesis of Amides Catalyzed by Bu4NI with TBHP as an Oxidant

Abstract: Scheme 4. Scope of the reaction with aryl aldehydes. Scheme 5. Scope of the reaction with other aromatic aldehydes. Scheme 6. Scope of the reaction with N,N-disubstituted formamides. 2.0 mL of ethyl acetate was used for 9 f. N.O = not obtained Angewandte Chemie 3233

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
118
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(121 citation statements)
references
References 145 publications
3
118
0
Order By: Relevance
“…[6] The transformation of aldehydes into esters and amides in one step is an attractive goal that has been pursued using precious-metal catalysts, [7] base-metal catalysts with strong oxidants, [8] and N-heterocyclic carbene (NHC) catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] The transformation of aldehydes into esters and amides in one step is an attractive goal that has been pursued using precious-metal catalysts, [7] base-metal catalysts with strong oxidants, [8] and N-heterocyclic carbene (NHC) catalysis.…”
mentioning
confidence: 99%
“…However, when using the same method at slightly elevated temperatures (40 8C), amide bond formation was observed using aniline nucleophiles (Scheme 3). Thus, we can convert aldehydes into amides using base-metal catalysis without relying on highly reactive reagents, such as peroxides [8] or aryl azides. [16] Under these conditions, aldehydes containing electron-donating (7 b, 93 %) or -withdrawing (7 c, 97 %) groups reacted efficiently, as well as aldehydes that would be sensitive to peroxide oxidants (7 d, 91 %).…”
mentioning
confidence: 99%
“…Iodide was initially oxidized by TBHP to Na[IO] − , which was further oxidized to a key intermediate hypoiodite Na[IO 2 ] − (A) with one more equivalent of TBHP [33,34]. The oxidative addition of 2 at the α-position by A would give a key β-diester intermediate B, which readily experienced substitution by 1 to give the α-oxybenzoylation product 4 under mild conditions (60°C), releasing the catalyst precursor Na[IO] − .…”
Section: Resultsmentioning
confidence: 99%
“…Other solvents studied, such as DMF and DMSO, resulted in meaningless yields. Other oxidants were also employed, and 3a was not detected (Table 1, entries [14][15][16][17]. Besides, experiments also demonstrated that no 3a was formed in the absence of catalyst or oxidant (Table 1, entries 8 and 18).…”
Section: Resultsmentioning
confidence: 99%